Decreasing Operational Distortion and Surrogation Through Narrative Reporting - Bentley, Jeremiah W. (The Accounting Review, 2019)
ABSTRACT Prior research finds that agents who are compensated on an imperfect measure of performance tend to distort their operational decisions and believe that the measure is more reflective of reality than it actually is (i.e., they surrogate). I find that agents distort decisions less and surrogate less when they can provide unverifiable narrative explanations for their actions. In my experiment, experienced chess players place bets on and write explanations about in-progress chess games. I manipulate whether participants give their explanations to their boss (who allocates a subjective bonus) when working as an agent. Participants who give explanations are more likely to make bets that reflect all dimensions of a chess position, rather than making bets that favor only the objective measure. They are also less likely to surrogate and are more likely to write about unmeasurable aspects of the games when subsequently making bets on their own behalf.